2010
DOI: 10.1002/cbf.1702
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐lipoic acid does not alter stress protein response to acute exercise in diabetic brain

Abstract: Heat shock proteins (HSPs) are molecular chaperones which may act protective in cerebrovascular insults and peripheral diabetic neuropathy. We hypothesized that alpha-lipoic acid (LA), a natural thiol antioxidant, may enhance brain HSP response in diabetes. Rats with or without streptozotocin-induced diabetes were treated with LA or saline for 8 weeks. Half of the rats were subjected to exhaustive exercise to investigate HSP induction, and the brain tissue was analyzed. Diabetes increased constitutive HSC70 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Similarly, it was observed that the ferric nitrilotriacetate (Fe-NTA)-induced diabetes in rats was associated with an increase of HO-1 protein levels in the brain [127]. In addition, in another work, HO-1 mRNA expression in the brain of diabetic rats was unchanged with respect to the controls [128], thus leaving the information about HO-1 in the brain quite vague. Based on these data and our experience, it becomes difficult to argue a unique hypothesis about the role of HO-1 in insulin resistance in the brain because what is still missing with regard to diabetes is the data about HO activity and/or post-translational modifications.…”
Section: Oxidative Stress: Is It the Driving Force For Insulin Resmentioning
confidence: 99%
“…Similarly, it was observed that the ferric nitrilotriacetate (Fe-NTA)-induced diabetes in rats was associated with an increase of HO-1 protein levels in the brain [127]. In addition, in another work, HO-1 mRNA expression in the brain of diabetic rats was unchanged with respect to the controls [128], thus leaving the information about HO-1 in the brain quite vague. Based on these data and our experience, it becomes difficult to argue a unique hypothesis about the role of HO-1 in insulin resistance in the brain because what is still missing with regard to diabetes is the data about HO activity and/or post-translational modifications.…”
Section: Oxidative Stress: Is It the Driving Force For Insulin Resmentioning
confidence: 99%
“…HO-1 is a myocardial protection factor and has anti-inflammatory, anti-oxidant, anti-apoptotic and anti-arrhythmia properties. In addition, HO-1 has an important role in cardiovascular disease and research has demonstrated that HO-1 is able to inhibit cardiac hypertrophy; however, oxidative stress leads to DCM and results in the reduction of HO-1 expression (24,25). HO-1 expression has become a universal marker of protection against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%